Meningkatkan Literasi Keuangan dan Pengendalian Utang Pada UMKM di Kabupaten Pamekasan, Madura - Yudhanta Sambharakreshna; Fariyana Kusumawati; Nurul Kompyurini; Anis Wulandari (JANAKA : JURNAL PENGABDIAN MASYARAKAT KEWIRAUSAHAAN INDONESIA, 2025)
This community engagement program aims to strengthen financial literacy and debt management skills among Micro, Small, and Medium Enterprises (MSMEs). Field findings indicate that many entrepreneurs still struggle with fundamental aspects of financial management, such as recording transactions, distinguishing between personal and business funds, and developing repayment plans. To address these issues, the program applied a combination of awareness-building activities, training sessions, interactive simulations, and mentoring. Pre-test and post-test evaluations revealed significant improvements in participants’ ability to maintain daily cash flow records, prepare simple income statements, and design repayment schedules aligned with business cash flow. Furthermore, behavioral changes were evident, as participants began to separate business and personal finances through dedicated bank accounts or digital bookkeeping tools. The program’s positive effects extended beyond managerial skills, fostering greater confidence among business owners, improving access to formal financing, and enhancing collective awareness of financial literacy as a foundation for sustainable enterprises. These results demonstrate that structured and practical educational interventions can help MSMEs overcome recurring challenges related to capital and debt management, while simultaneously strengthening their competitiveness and long-term sustainability.Keywords: Financial Literacy, Debt Management, MSMEs, Cash Flow, Sustainability